The Effect of Peritoneal Air Exposure on Intestinal Mucosal Barrier - Jun Bao; Shanjun Tan; Wenkui Yu; Zhiliang Lin; Yi Dong; Qiyi Chen; Jialiang Shi; Kaipeng Duan; Xiaowu Bai; Lin Xu; Jieshou Li; Ning Li (Gastroenterology Research and Practice)
Background. Damage of the intestinal mucosa barrier may result in intestinal bacterial and endotoxin translocation, leading to local and systemic inflammation. The present study was designed to investigate whether peritoneal air exposure induces damage of intestinal mucosal barrier. Methods. Sprague-Dawley rats (weighing 210 to 230 g) were randomized into five groups (6/group): a control group, a sham group, and three exposure groups with peritoneal air exposure for 1, 2, and 3 h, respectively. At 24 h after surgery, blood and terminal ileum were sampled. The serum D-lactate levels were determined using an ELISA kit. The intestinal permeability was determined by measuring the intestinal clearance of FITC-dextran (FD4). The histopathological changes in terminal ileum were also assessed. Results. Compared with the controls, peritoneal air exposure caused an increase in both serum D-lactate level and intestinal FD4 clearance, which were proportional to the length of peritoneal air exposure and correlated to Chiu’s scores, indices for intestinal mucosal injury. Edema and inflammatory cells were also observed in mucosa and submucosa of ileum in three exposure groups. Conclusions. Peritoneal air exposure could induce damage to the intestinal mucosal barrier, which is proportional to the time length of peritoneal air exposure.